2021
DOI: 10.1177/13634615211022177
|View full text |Cite
|
Sign up to set email alerts
|

Mental health literacy in Ghana: Implications for religiosity, education and stigmatization

Abstract: Research on Mental Health Literacy (MHL) has been growing internationally. However, the beliefs and knowledge of Ghanaians about specific mental disorders have yet to be explored. This vignette study was conducted to explore the relationships between religiosity, education, stigmatization and MHL among Ghanaians using a sample of laypeople (N = 409). The adapted questionnaire presented two vignettes (depression and schizophrenia) about a hypothetical person. The results revealed that more participants were abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 75 publications
1
13
0
1
Order By: Relevance
“…Although the results of the qualitative FGD showed a reduction in self-stigma among participants, however, the quantitative changes in stigma tolerance were not maintained at 2 months follow-up, which may suggest the need for a booster session. This is similar to the findings in a study in Ghana on the impact of MHL on stigma tolerance [ 81 ] which indicates that a higher threshold level of MHL must be reached before changes in an individual’s indifference to stigma becomes apparent.…”
Section: Discussionsupporting
confidence: 88%
“…Although the results of the qualitative FGD showed a reduction in self-stigma among participants, however, the quantitative changes in stigma tolerance were not maintained at 2 months follow-up, which may suggest the need for a booster session. This is similar to the findings in a study in Ghana on the impact of MHL on stigma tolerance [ 81 ] which indicates that a higher threshold level of MHL must be reached before changes in an individual’s indifference to stigma becomes apparent.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, Adu et al. ( 2021 ) found the level of education positively associated with higher MHL among Ghanaians, while it was agreed by Öztas and Aydoğan ( 2021 ) that healthcare professionals had higher MHL as a result of their education level. Linden and Kavanagh ( 2012 ) found that PHC nurses with less training as well as little exposure and experience in mental health had negative, prejudiced, and fearful attitudes toward and perceptions of people with mental health problems.…”
Section: Discussionmentioning
confidence: 96%
“…Mental health literacy. Questions about MHL were adapted from the Australian National Survey of Mental Health Literacy and Stigma (Reavley & Jorm, 2011a, 2011b, widely used in many international studies (Adu et al, 2021;Thai & Nguyen, 2018). The MHL questions are based on a vignette of a person with a mental disorder.…”
Section: Methodsmentioning
confidence: 99%